PROCESSING OF SAWDOW WASTE OF MAHONI AND JATI WOOD AS A MATERIAL GYPSUM CEILING FILLERS WITH POLIVINYL ADHESIVE ALCOHOL - Zai, Liver; Halawa, Estetika Niat Iman; Tarigan, Malemta; Gultom, Erdiana; Purwandari, Vivi; Jiamin, Ong Amanda (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2023)
Along with the increase in population, the need for building materials, namely wood, will increase, thus triggering rampant illegal logging, which will cause floods, landslides, and global warming. One of the efforts made to reduce the use of wood is to make gypsum composite boards. This study aims to utilize mahogany wood waste and jati wood powder as gypsum board fillers. Research has been carried out on processing waste sawdust from mahogany and jati wood as a filling material for making gypsum ceilings with polyvinyl alcohol adhesive by mixing and compacting using a hot compressor at 70o C. Good quality with a density value of 0.82 g /cm3 and absorption capacity of 38.4% complied with SNI 03-2105-2006. Mechanical properties with variations in impact strength (95:5:10) of 19.014 J/m2, flexural strength of variation (95:5) of 395, 446 N/m2, and fracture strength of variation (95:5:5) of 1.7758 N/m2. A Gypsum board was obtained, which did not meet SNI 03-6384-2000 on the gypsum board specification for the results of testing for flexural strength and fracture strength.